On the material characteristics of a high carbon cast austenitic stainless steel after solution annealing followed by quenching in a CNT nanofluid - Pour-Ali, Sadegh; Kiani-Rashid, Ali-Reza; Babakhani, Abolfazl; Virtanen, Sannakaisa; Nguyen, Nhat Truong; Hejazi, Seyedsina; Davoodi, Ali; Nazarnejatizadeh, Afshin; Teimourinejad, Hashem (International Journal of Materials Research, 2019)
Solution annealing followed by quenching in carbon nanotubes (QCNT) nanofluid treatment was applied to generate very high interstitial carbon content, approximate to 0.30 wt.%, in an austenitic stainless steel (ASS). The high interstitial carbon content leads to remarkable improvement in mechanical properties with essentially no loss of ductility, with no chromium carbides and/or martensite formation. To evaluate the localized corrosion tendency and passivity behavior, 3.5 wt.% NaCl and borate buffer solutions were used, respectively. Based on the electrochemical corrosion results, both high carbon and low carbon (0.030 wt.%) QCNT-treated ASS alloys show comparable passivity and localized corrosion performance. In addition, Mott-Schottky plots revealed that the anodic films on QCNT-treated samples exhibit similar semiconducting characters.
CRIS-Team WoS Importer:2019-06-28